IMPLEMENTASI KOMUNIKASI EFEKTIF TERHADAP KELENGKAPAN GENERAL CONSENT RAWAT INAP DI UNIT REKAM MEDIS RUMAH SAKIT KRISTEN MOJOWARNO JOMBANG PROVINSI JAWA TIMUR - saraswati satya kusumaningrum (Health Care Media, 2022)
General consent is a statement of consent to receive health services obtained from a person during the intake process at the initial visit, before receiving health services, this thesis is the result of a study that describes how much influence the officer's communication regarding general consent has on patients which resulted in many things found in September 2021, there were 20 general consents found in September 2021. incomplete hospitalizations of 67% of the 30 patients were found in the type of payment, the signature of the officer, and the name of the officer 's light "regarding the rights and obligations contained in the general consent. The design of this study refers to the descriptive stage of qualitative analytics. The data analysis used is interview and source triangulation. The medical record officer of Mojowarno Jombang Christian Hospital is responsible for supervising and evaluating, coordinating the filling out of the inpatient general consent form, and auditing it to ensure it is filled out correctly and the patient's family knows the purpose. We recommend that effective communication should be implemented, because effective communication training has been provided to support the delivery of information to patients. Keywords: Effective Communication, General Consent, Medical Record Unit.